Optimization of Membership Functions for the Fuzzy Controllers of the Water Tank and Inverted Pendulum with Differents PSO Variants - Resffa Fierro; Oscar Castillo; Fevrier Valdez; Patricia Melin (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
In this paper the particle swarm optimization metaheuristic and two of its variants (inertia weight and constriction coefficient) are used as an optimization strategy for the design of optimal membership functions of fuzzy control systems for the water tank and inverted pendulum benchmark problems. Each variant has its own advantages in the algorithm, allowing the exploration and exploitation in different ways and this allows finding the optimal solution in a better way.